In-vitro antioxidant and cytotoxicity screening of ethanolic extract of lagerstroemia thorelli (Lythraceae) leaves - Tipu, Amir Hamja (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.